Mengenal Pemikiran Islam liberal - Aprilia Mawaddah; Muhammad Rizki Amin; Pebriana Pebriana; Agus Rifki Ridwan (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Liberal Islamic philosophy is a contemporary concept within the Islamic world, arising as a counter to the prevailing association of Islam with radicalism, terrorism, and bloodshed. This new philosophy has a more lenient stance towards Islam's normative beliefs, aiming to engage with the perspectives of orthodox or fundamentalist Islamic organizations. This has provoked both favorable and adverse reactions to the theory. This page aims to portray liberal Islamic thinking academically and objectively, without taking a side in the controversies. The discourse encompasses the concept, aims, and epistemological framework of liberal Islam. The importance of this study stems from the perspectives of observers of Islamic thinking who either support or oppose liberal Islamic philosophy without offering a comprehensive comprehension of its fundamental notions.